Scientific publication and characteristics of the thesis advisers of a peruvian psychology school - Mamani Benito, Oscar J. (2019)
The objective of this study was to describe the characteristics of undergraduate thesis advisors in a psychology school and analyze their scientific production. The methodology involves a descriptive-bibliometric study, where the study population was 37 teacher advisors of 149 undergraduate projects approved at a private university in Peru. These were placed in the institution's repository and approved in the period from 2014-2017. The main results indicate that there was greater participation of women advisers (70.3%) than men (29.7%), in addition, 64.9% had only a professional title (undergraduate degree), 21.6% a master's degree and only 13.5% a doctorate degree. Likewise, only 27% evidence scientific publications in Google Scholar, while 73% did not publish sometime in their life; finally, we found a scientific production of 37 articles published (33 originals, 2 letters to the editor and 2 editorials) corresponding to 10 advisory teachers, in national and international journals. In conclusion, the undergraduate thesis advisors in psychology have a worrying and low level scientific production.